Education on Improving Dental Health Maintenance for Students : Edukasi Peningkatan Pemeliharaan Kesehatan Gigi Santri - Anita Yulviyani; Sabda Alam; Febria Desi; Dian Artanty; Cinitra Anindya; Adi Cahyo; Anindita Zahratur; Bingah Fitri; Ratna Mustriana; Febriyanti Kusuma; Aryo Sutowijoyo; Rangga Surya; Bandaru Rahmatari; Prima Nerito; Meirna Dewita; Yeni Puspitasari; Khamila Gayatri; Angeline Musmarihan (KHD Production, 2025)
Dental and oral health problems, especially tooth decay, are diseases experienced by almost half of the world's population. Indonesia's most significant dental problems are damaged/cavities/painful teeth. One of the promotive efforts to maintain and improve the degree of dental and oral health in the community is through counseling. International Islamic Boarding School (IIBS) Baitul Manshurin Malang which does not yet have health service facilities. Health education programs are rarely conducted by healthcare workers or the local health department. Therefore, a community service program was realized at IIBS Baitul Manshurin Malang in the form of counseling aimed at increasing knowledge about dental and oral health maintenance. 350 The male and female students took a pre-test first to assess their knowledge, attitudes, and practices regarding dental health maintenance. Conducted counseling and concluded with a post-test to determine whether there was an improvement in the knowledge, attitudes, and actions of the male and female students. The pre-test data shows that 45.1% of the students at IIBS Baitul Manshurin fall into the moderate category. The post-test results show an increase in the percentage of the good category, from 13.1% to 20.6%, and a decrease in the percentage of the bad category, from 41.7% to 26%. The outreach activities have a positive impact on the knowledge, attitudes, and actions of the students at IIBS Baitul Manshuri.